The price of death [videorecording (DVD)] - Belfrage, Crispian; Luckey, Ken; Stielstra, Aaron (Octane Multimedia, 2025)
A gambler turned bounty hunter transports a high-priced outlaw, unaware that they are being chased by a ruthless murderer and his gang of thieves for money hidden by the outlaw. The final film of Al Mathews (Sgt. Apone from Aliens 1986), who passed away in Alicante, Spain in 2018. Filmed in Mini Hollywood, Tabernas, Almeria, Andalucia, Spain.